Endotrophin neutralization through targeted antibody treatment protects from renal fibrosis in a podocyte ablation model - Yu A. An; Wei Xiong; Shiuhwei Chen; Dawei Bu; Joseph M. Rutkowski; Joel P. Berger; Christine M. Kusminski; Ningyan Zhang; Zhiqiang An; Philipp E. Scherer (Elsevier, 2023)
Objective: Renal fibrosis is a hallmark for chronic kidney disease (CKD), and often leads to end stage renal disease (ESRD). However, limited interventions are available clinically to ameliorate or reverse renal fibrosis. Methods: Herein, we evaluated whether blockade of endotrophin through neutralizing antibodies protects from renal fibrosis in the podocyte insult model (the "POD-ATTAC" mouse). We determined the therapeutic effects of endotrophin targeted antibody through assessing renal function, renal inflammation and fibrosis at histological and transcriptional levels, and podocyte regeneration. Results: We demonstrated that neutralizing endotrophin antibody treatment significantly ameliorates renal fibrosis at the transcriptional, morphological, and functional levels. In the antibody treatment group, expression of pro-inflammatory and pro-fibrotic genes was significantly reduced, normal renal structures were restored, collagen deposition was decreased, and proteinuria and renal function were improved. We further performed a lineage tracing study confirming that podocytes regenerate as de novo podocytes upon injury and loss, and blockade of endotrophin efficiently enhances podocyte-specific marker expressions. Conclusion: Combined, we provide pre-clinical evidence supporting neutralizing endotrophin as a promising therapy for intervening with renal fibrosis in CKD, and potentially in other chronic fibro-inflammatory diseases.